The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7547/20-058
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Porcine-Derived Xenograft as an Adjunct to Split-Thickness Skin Grafting in Lower-Extremity Wounds

Abstract: Objective Porcine-derived xenograft biological dressings (PXBDs) are occasionally used to prepare chronic wound beds for definitive closure before split-thickness skin grafts (STSGs). We sought to determine whether PXBD influences rate of STSG take in lower-extremity wounds. Methods Lower-extremity wounds treated with STSGs were retrospectively reviewed. Patients were included in one of two groups: wound bed preparation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…CHSA decreases pain, stimulates angiogenesis, prepares the wound bed for autografting, controls infection, and is low cost but confers the risk of disease transmission ( 123 ). Xenografts such as fish skin grafts promote efficient wound healing, but potential of rejection must be considered ( 90 , 93 , 94 ). Lastly, tissue engineered skin substitutes such as BLCC and DRT promote healing but provide the challenge of cost ( 97 , 124 , 125 , 129 , 131 , 132 , 157 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHSA decreases pain, stimulates angiogenesis, prepares the wound bed for autografting, controls infection, and is low cost but confers the risk of disease transmission ( 123 ). Xenografts such as fish skin grafts promote efficient wound healing, but potential of rejection must be considered ( 90 , 93 , 94 ). Lastly, tissue engineered skin substitutes such as BLCC and DRT promote healing but provide the challenge of cost ( 97 , 124 , 125 , 129 , 131 , 132 , 157 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, xenografts confer the advantages of being lower cost, in unlimited supply, and having lower risk of disease transmission than their allograft counterparts (92). Xenografts used in the treatment of chronic wounds include porcine, bovine, and more recently, fish (94,95). A major advantage of the use of fish skin grafts over other types of xenografts include lower risk of viral transmission, enabling mild processing that preserves skin integrity which contains beneficial collagen, elastin, and Omega-3 polyunsaturated fatty acids thought to improve reepithelialization and microbial defense (93,96,97).…”
Section: Xenograftsmentioning
confidence: 99%
“…Porcine xenograft has been used for wound bed preparation with the hope of improving the take of skin autograft over burn and nonburn wounds [3,4]. A recently published article [5] compared the use of porcine xenografts with no specific method for wound bed preparation and concluded that there was no difference in these two methods in terms of wound closure. But the author's experience differs from this study.…”
Section: Porcine Xenograftmentioning
confidence: 99%